2015
DOI: 10.1016/j.jphotochem.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of P3HT and PC 60 BM in toluene solution: Evidence of T–T energy transfer

Abstract: A B S T R A C TPhotochemical properties of regioregular poly(3-hexylthiophene) (P3HT), fullerene derivative [6,6]-phenyl C61-butyric acid methyl ester (PC 60 BM) and their 1:1 mixture in argon-saturated toluene solution were studied by optical spectroscopy and nanosecond laser flash photolysis (l ex = 532 nm). Separate excitation of components leads to formation of corresponding triplet state of fullerene (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Moreover, their photophysical properties are well characterized in the literature. It has been shown that energy transfer from P3HT to fullerenes and carbon nanotubes occurs in solution 29,30 and in the solid-state, 31,32 and that such blends can produce singlet oxygen. 20 Here, P3HT is assumed to act both as support for the carbon-based photosensitizers and as a visible-light antenna.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, their photophysical properties are well characterized in the literature. It has been shown that energy transfer from P3HT to fullerenes and carbon nanotubes occurs in solution 29,30 and in the solid-state, 31,32 and that such blends can produce singlet oxygen. 20 Here, P3HT is assumed to act both as support for the carbon-based photosensitizers and as a visible-light antenna.…”
Section: Introductionmentioning
confidence: 99%